A Syllabi Analysis of Social Media for Teaching and Learning Courses - Enilda Romero-Hall; Linlin Li (University of Windsor, 2020)
The purpose of this syllabi analysis was to explore the structure of courses focused on social media and geared towards education professionals. Fourteen course syllabi from institutions located within the United States (U.S) were analyzed as part of this investigation. The results of the analysis revealed a total of 46 unique topic themes across the different courses. The findings show that the most common course objectives aimed to encourage application and practice of social media as part of a learning experience and the learners' professional practice. In total, the syllabi listed 67 unique required readings including: non-peer reviewed publications, peer-reviewed journal articles, and textbooks. Last, the analysis of the assignments listed in the syllabi show that in these social media courses, there were a mix of traditional and non-traditional assessment methods. These non-traditional assessment methods focused on integrating social media as part of the assessment in which learners were required to create a social media account, become familiar with it, and create learning experiences incorporating a specific social media platform.